Test of The Inhibitory Power of Lemongrass Extract Against The Growth of Candida albicans On Natural Resources Medium - Murtafi'ah, Ni'matul; Syarofah, Zela Adeline; Pitono, Arie J. (Lighthouse Publishing, 2022)
Candidiasis is an acute or chronic inflammation that causes disorders of the body's system caused by the fungus Candida albicans. Candida albicans is a common cause that does not cause disease in a person's normal immune system but can attack a person's poor system. Candidiasis can be treated with antifungal drugs, but prolonged and extensive use of antifungal drugs causes side effects. So alternative drugs are needed that can reduce these side effects. Lemongrass (Cymbopogon citratus) has pharmacological activity as an antifungal. Research Objectives: To determine the inhibition of lemongrass extract on the growth of Candida albicans in an SDA medium with concentrations of 0%, 0.2%, 0.4%, 0.6%, 0.8%, and 1%. The study used a descriptive research design. The method of testing the resistance is carried out by the good diffusion method. Lemongrass extract can inhibit the growth of Candida albicans fungus by forming an inhibition zone. At a concentration of 0% lemongrass extract, no inhibition zone was formed, a concentration of 0.2% formed an inhibitory zone of 10.5 mm, a concentration of 0.4% formed an inhibition of 6.1 mm, a concentration of 0.6% formed an inhibition zone of 14 mm, the concentration 0.8% formed an inhibition zone of 10.8 mm, a concentration of 15 formed an inhibitory zone of 27.6 mm.